Chilblains during lockdown are associated with household exposure to SARS-CoV-2: a multicentre case–control study. (February 2022) - Poizeau, Florence; Oger, Emmanuel; Barbarot, Sébastien; Le Corre, Yannick; Samimi, Mahtab; Brenaut, Emilie; Aubert, Hélène; Chambrelan, Estel; Droitcourt, Catherine; Gissot, Valérie; Heslan, Christopher; Laurent, Claire; et al.
Abstract: Objectives: During the COVID-19 pandemic, numerous cases of chilblains have been reported. However, in most cases, RT-PCR or serology did not confirm SARS-CoV-2 infection. Hypotheses have been raised about an interferon-mediated immunological response to SARS-CoV-2, leading to effective clearance of the SARS-CoV-2 without the involvement of humoral immunity. Our objective was to explore the association between chilblains and exposure to SARS-CoV-2. Methods: In this multicentre case–control study, cases were the 102 individuals referred to five referral hospitals for chilblains occurring during the first lockdown (March to May 2020). Controls were recruited from healthy volunteers' files held by the same hospitals. All members of their households were included, resulting in 77 case households (262 individuals) and 74 control households (230 individuals). Household exposure to SARS-CoV-2 during the first lockdown was categorized as high, intermediate or low, using a pre-established algorithm based on individual data on symptoms, high-risk contacts, activities outside the home and RT-PCR testing. Participants were offered a SARS-CoV-2 serological test. Results: After adjustment for age, the association between chilblains and viral exposure was estimated at OR 3.3, 95% CI (1.4–7.3) for an intermediate household exposure, and 6.9 (2.5–19.5) for a high household exposure to SARS-CoV-2. Out of 57 case households tested, six (11%) had positive serology for SARS-CoV-2, whereas all control households tested ( n = 50) were seronegative ( p = 0.03). The effect of potential misclassification on exposure has been assessed in a bias analysis. Discussion: This case–control study demonstrates the association between chilblains occurring during the lockdown and household exposure to SARS-CoV-2.